BIO011: Biology for Pre Diploma I / Faculty of Applied Sciences - UiTM, Faculty of Applied Sciences (2020)
This course involves the basic concepts and principles of biology that covers the surface information about cells structure, component and function, basic animal and plant tissue, structure and function, organ structures and functions, basic concept of nutrition in organism such as digestive process in human and photosynthesis process in plant. Throughout the course, students will be equipped with basic knowledge in biology that is very important for detailed learning process at diploma and degree level.